Correlating the Impact of Project Oversight on U.S. Navy Construction Projects - Lawrenz, Heidi (My University, 2019)
ABSTRACT Limited analysis has been conducted to quantify the effects of Owner project oversight† on construction projects, particularly in the public sector. The intent of this research project is to correlate project oversight provided on construction projects with the performance of the project, thus quantifying claims from construction and project management† experts that project Owner involvement has an effect on project outcome. In order to test this hypothesis, data from a sample of construction projects from Naval Facilities Engineering Command (NAVFAC), the U.S. Navy’s public works and construction management lead, was collected via NAVFAC’s project database and through a survey of NAVFAC Construction Managers† (CMs) and Engineering Technicians† (ETs) who provided the oversight on the projects. A 5-point Likert scale was utilized to measure the degree of effort CMs and ETs provided on a project. NAVFAC’s six Focus Areas were selected as performance metrics, and were measured and compiled into single scores using a methodology similar to El Asmar, et al.’s ‘Project Quarterback Rating.’ Statistical analysis was then utilized to determine if a correlation exists between the degree of oversight provided on various owner tasks and project performance metrics such as cost growth, schedule growth, safety, quality, and stakeholder satisfaction. Increased effort provided on change management tasks resulted in a negative correlation with performance metrics. Coordination of power outages and phasing, Quality Assurance tasks, etc. resulted in a positive correlation with performance metrics. Years of respondent construction experience, turnover of the CM or ET during the construction project, and an unbalanced workload for the CM or the ET also positively correlated with project performance metrics. Last, project characteristics were tested to determine if there was a correlation between certain characteristics and project performance. Characteristics that were positively correlated were controlled for and like projects binned into categories, and each of these bins was then re-tested to determine under which conditions project oversight correlates with project performance. For project with smaller durations and costs, project oversight had a positive correlation with quality and stakeholder satisfaction. For intermediate- or large-sized projects overall performance score was correlated. When controlling for number of project complications outside the control of the Owner’s CM or ET, cost growth and schedule growth showed a positive correlation with oversight provided, likely indicating that despite additional effort, the negative effects on cost and schedule growth of project complications overruled the positive effects of CM or ET engagement. However, overall project performance score showed a positive correlation with additional project oversight for projects with many complications.
Keywords: construction; project oversight; project outcome; project management